INTERLANGUAGE (ENGLISH-UZBEK, ENGLISH-RUSSIAN) SPECIFICITIES - Axmadjonova Oydinoy; Moydinova Sh (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract This article explores the phenomenon of interlanguage with specific focus on the interactions between English and two commonly learned languages in Uzbekistan: Uzbek and Russian. It outlines the distinctive linguistic influences, transfer errors, and pedagogical challenges that emerge during second language acquisition. The paper also offers methodological insights for educators teaching English to Uzbek and Russian- speaking learners.